2018
DOI: 10.24017/science.2018.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Effect of milk proteins aggregation using Transglutaminase and Maillard reaction on Ca2+ milk gel

Abstract: Effect of transglutaminase, Maillard reaction induced crosslinking and the combination of transglutaminase and Maillard reaction induced crosslinking between whey proteins and caseins in milk on calcium milk gel properties were investigated. Treatment of milk with transglutaminase, Maillard reaction, and transglutaminase + Maillard reaction cause to the appearance of new high MW protein bands.  Water holding capacity, gel strength and sensory scores of gel samples increased and spontaneous whey separation decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The effect of aggregation of milk proteins using TGAse and MR on Ca 2+ milk gel has been studied by Alfayadh et al ( 2018 ) who found that the total scores were 80.6, 75.3, 84.3, and 83.1 for the control gel, Maillard‐modified milk, milk treated with TGAse, and milk treated with Maillard/TGAse after 1 day of storage at 7°C, which changed to 80, 78.5, 90.5, and 89.5, respectively, at the end of the storage period at 7°C. Among all milk calcium gels, the gel prepared from Millard's modified milk obtained the lowest sensory score from the panelists, which is probably due to the separation of whey in the top layer of the gel.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of aggregation of milk proteins using TGAse and MR on Ca 2+ milk gel has been studied by Alfayadh et al ( 2018 ) who found that the total scores were 80.6, 75.3, 84.3, and 83.1 for the control gel, Maillard‐modified milk, milk treated with TGAse, and milk treated with Maillard/TGAse after 1 day of storage at 7°C, which changed to 80, 78.5, 90.5, and 89.5, respectively, at the end of the storage period at 7°C. Among all milk calcium gels, the gel prepared from Millard's modified milk obtained the lowest sensory score from the panelists, which is probably due to the separation of whey in the top layer of the gel.…”
Section: Resultsmentioning
confidence: 99%
“…Sensory evaluation form was used for yoghurt samples on the first day and 21 days stored at 7 ± 1°C. Finally, sensory properties, including flavor, texture, acidity, appearance, and total acceptance yoghurt samples, were evaluated based on 100 points (Alfayadh et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation